Understanding Sharon Olds - Brickey, Russell (Book collections on Project MUSE., 2016)
"Understanding Sharon Olds explores this Pulitzer Prize-winning poet's major themes, characters, life, and career, including her often-controversial portrayals of family dysfunction, sexuality, and violence against women. In this first book dedicated entirely to the poetry of Sharon Olds, Russell Brickey examines how Olds approaches these difficult and complex topics with pathos and intimate, sometimes provocatively private, details through poetry that not all her critics appreciate. Olds has never shied away from difficult subject matter. Her first award-winning book, Satan Says, is a feminist exploration of gender politics and adolescent discovery. The Father comprises a book-length elegy about cancer. Stag's Leap, Olds's Pulitzer Prize-winning volume, is a surprisingly tender look at divorce in modern American culture. Extremely personal, her poems often deal with the victories and contradictions of being a woman in the United States during a time when the country is often involved in racial upheavals and military conflicts overseas. She investigates the victories and contradictions of being a wife and mother during the era of feminism, as one of our most honest, most overt poets of female sexuality and its relationship to family life and its place within the history of humanity. Brickey organizes each chapter around a theme or a persona within Olds's cast of characters. These include poems dedicated to mothers, fathers, children, and the arc of history. Through his close readings, Brickey shows how and where Olds has expanded the tradition of confessional poetry (literature that deals with psychology, family, love, and sexuality), a term Olds disdains but nevertheless expanded into commentary about the human condition in all its paradoxes."--